The Implementation of Non-Cash Food Assistance Program (BPNT): A Case Study of Apela Satu Sub-District, Ranowulu District, Bitung City - Pangemanan, Sandra Elisabeth; Dilapanga, Abdulrahman; Mamonto, Fitri (Technium Social Sciences Journal, 2023)
This research is motivated by the government program known as the Non-Cash Food Assistance Program (BPNT) in Apela Satu sub-district, Ranowulu district, Bitung city. This assistance program has been implemented since 2017, initially known as the Family Welfare Program (RASTRA). The distribution process of BPNT is done in a non-cash manner with the aim of fulfilling the 6 Ts criteria: Targeted, Administrative Accuracy, Timeliness, Targeted Beneficiaries, Benefits Accuracy, and Quality Accuracy. However, it has been found in the field that some economically capable individuals are still registered as beneficiaries, while there are economically disadvantaged individuals who are not registered as recipients. This situation does not meet one of the 6 Ts criteria, which is targeting accuracy. The research methodology used in this study is qualitative, which formulates the discussion results using descriptive data. The data is obtained through field observations, directly observing the lives of the aid recipients, documentation, and interviews. The purpose of this research is to understand the implementation of the Non-Cash Food Assistance Program (BPNT). The results of the discussion and analysis of this research indicate that the implementation of BPNT is structurally implemented and contributes to the economic well-being and food sufficiency of the beneficiary community.